2010
DOI: 10.1007/s11426-010-4093-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perfluorinated compounds in seven wastewater treatment plants in Beijing urban areas

Abstract: The presence of perfluorinated compounds (PFCs) in seven major wastewater treatment plants (WWTPs) in Beijing was investigated in the current study. We detected nine PFCs in all the wastewater and sludge samples. Perfluorooctane acid (PFOA) is the dominant PFCs in influents and effluents, while perfluorooctane sulfonate (PFOS) is the major contaminant in sludge. The highest PFC concentration was found in plants at Qinghe and Jiuxianqiao WWTP, while the lowest was found at Fangzhuang WWTP. The total values of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 31 publications
3
15
2
Order By: Relevance
“…PFOS was the dominant analyte in dewatered sludge samples from both WWTPs, as it was detected in 100% of collected samples. This result was similar to previous studies [9,10,12,28,29], but different from Sinclair and Kannan [8], who found that PFOA was the dominant PFC in sludge. PFOA was detected in all samples, except from three occasions.…”
Section: Pfcs In Sludge Samplessupporting
confidence: 86%
See 1 more Smart Citation
“…PFOS was the dominant analyte in dewatered sludge samples from both WWTPs, as it was detected in 100% of collected samples. This result was similar to previous studies [9,10,12,28,29], but different from Sinclair and Kannan [8], who found that PFOA was the dominant PFC in sludge. PFOA was detected in all samples, except from three occasions.…”
Section: Pfcs In Sludge Samplessupporting
confidence: 86%
“…Moreover, previous studies reported that the concentrations of other PFCs (PFNA, PFUdA, PFHxS) ranged from <LOD to <400 ng L −1 [7,8,12,[25][26][27][28]. On the other hand, the concentrations of PFPeA detected in this study were significantly higher than those previously reported [13].…”
Section: Pfcs In Wastewater Samplescontrasting
confidence: 76%
“…In fact, in some cases it is often common to observe a phenomenon of negative removal or in-plant production [88]. Pan et al [89] suggested the same fate when confronted with overall higher levels of PFCs in the effluents comparing to the influent flows. According to Heidler and Halden [88], several mass balances performed for fluorochemicals also reflect a net mass flow increase at the WWTP effluents.…”
Section: Perfluorinated Compoundsmentioning
confidence: 99%
“…However, this family of compounds have dissimilar behaviour among them, depending on the functional groups [90]. For instance, some authors reported that perfluorooctanesulfonic acid or perfluorooctane sulfonate (PFOS) levels have a decreasing tendency after treatment in most WWTPs, whilst perfluorooctanoic acid or perfluorooctanoate (PFOA) showed an inverse pattern [89][90][91]. According to Guo et al [90], this could be due to the higher organic carbon-normalised distribution coefficient of perfluoroalkylsulfonate (PFASs) in comparison with the carboxylate analog, a sign of preferential uptake of PFASs by the sludge, which seems to be a key mechanism in the process.…”
Section: Perfluorinated Compoundsmentioning
confidence: 99%
“…The mass loads of PFOA, PFOS, perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA) and perfluoroundecanoic acid (PFUnDA) were found increased in the secondary biochemical treatment of a WWTP due to the biodegradation of precursors (Sinclair and Kannan, 2006). Concentrations of PFASs varied greatly among different WWTPs, and most studies focused on the activated sludge process (Bossi et al, 2008;Murakami et al, 2008;Guo et al, 2010;Pan et al, 2011;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%